Assessment of antibiotic residues in chicken meat - Heba M. Kamouh; Reda Abdallah; Ghada A. Kirrella; Nader Y. Mostafa; Saleh Shafik (Open Veterinary Journal, 2024)
Background: Nowadays Veterinarians and poultry producers use antibiotics to increase growth rates, bird health, and feed efficiency, egg production, for preventative and therapeutic purposes, and to lessen the prevalence of poultry diseases. Most poultry producers have used a variety of antibiotics, either with or without veterinarian instruction. Although antibiotics are beneficial for the majority of their uses, their unauthorized use has resulted in residues accumulated in poultry products intended for human consumption which represent a serious risk to the general public that could be toxicological, microbiological or immunological. Aim: This study aimed at estimation of the residues of three major antimicrobial used in the intensive chicken rearing systems in Egypt, namely Oxytetracycline, Gentamicin, Ciprofloxacin. Moreover, the effect of cooking on such residues was investigated. Methods: A total of 100 chicken meat samples (breast, thigh, gizzard, liver, 25 each) were examined for detection of the aforementioned antimicrobials using the microbial inhibition assay and HPLC. Besides, samples containing the highest antimicrobial residues were examined for the effect of boiling for 30 min on such residues. Results: The obtained results revealed that 23%, 21%, and 17% of the examined samples were positive for oxytetracycline, gentamicin, and ciprofloxacin residues, respectively. As for cooking (boiling) for 30 minutes showed reduction of the antibiotic residue by 88.2%, 95.2%, and 31.3%, respectively. Conclusion: Antimicrobial residues were detected in the chicken meat parts retailed in Egypt. Cooking can reduce the antimicrobial residues at least in part. [Open Vet J 2024; 14(1.000): 438-448]